1961
DOI: 10.1172/jci104270
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Radioactive Phosphorus Into the Phospholipids of Human Leukemic Leukocytes and Platelets*

Abstract: The phospholipid composition of human platelets and erythrocytes has been reported by several investigators (1-4) and the metabolism of phospholipids in human blood has been studied in some detail (5-9). Recent investigations of phospholipid metabolism of leukocytes have been reported (6, 10) but we are not aware of similar studies on platelets.In this laboratory, investigation of the biochemical characteristics of leukemic leukocytes is being carried out, and as part of this program an examination of the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1963
1963
1997
1997

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…These studies extend those previously reported in which it was found that 'POL is incorporated rapidly into phosphatidic acid and phosphoinositide in platelets in vitro (1). (52) have reported that platelets can synthesize phospholipids de novo from labeled a-glycerophosphate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These studies extend those previously reported in which it was found that 'POL is incorporated rapidly into phosphatidic acid and phosphoinositide in platelets in vitro (1). (52) have reported that platelets can synthesize phospholipids de novo from labeled a-glycerophosphate.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that human platelets incorporate radioactive phosphate into phospholipids both in vivo and in vitro (1)(2)(3)(4)(5). In the in vitro studies, phosphatidic acid and phosphatidylinositol were labeled more rapidly than other phosphatides, suggesting that these compounds were synthesized rapidly and that they might be responsible for some important metabolic function.…”
Section: Introductionmentioning
confidence: 99%
“…In this e)-periment, the radioactivity in PS remained constant after the first 30 min and did not decrease significantly (3). Previous studies using 'P incorporation suggested that circulating platelets might synthesize phospholipid as well (6). In these studies, Firkin and Williams suggested that phosphatidic acid and phosphatidyl inositol were metabolically the most rapidly turning over lipids in platelets, although they were unable to determine whether net synthesis occurred.…”
Section: Methodsmentioning
confidence: 96%
“…Later, it became apparent that in various other tissues, liver (5,6), erythrocytes (7,8), leukocytes (9)(10)(11), and kidney (5,12), the in vitro incorporation of 'Pt was at a very high rate in the inositides.…”
Section: Introductionmentioning
confidence: 99%